The Impact of Sugar Intake, Household Income, and Maternal Education on the Occurrence of Dental Caries in Children: A Meta-Analysis - Arddha Maha Pawitra Dwi Puspita Dewi; Eti Poncorini Pamungkasari; Bhisma Murti (Masters Program in Public Health, 2024)
Background: In Indonesia, the prevalence of dental caries in early childhood is still very high, around 93%. This study aims to analyze and estimate the magnitude of the relationship between sugar consumption, family income, and maternal education and the incidence of dental caries in children, through a meta-analysis of primary studies conducted by previous authors. Subjects and Method: This study is a systematic review and meta-analysis using PICO as follows, Population: children aged 1 to 5 years 11 months, Intervention: high sugar consumption, high family income, high maternal education, Comparison: low sugar consumption, low family income, low maternal education, and Outcome: dental caries. The articles used in this study were obtained from three databases, namely PubMed, Google Scholar, and Science Direct, using the keywords